The Middle East and Eastern Africa intersected: Discussing contemporary connections - Ajú, M. M.; Ylönen, A. (Cadernos de Estudos Africanos, 2022)
Historically, the interaction between the Middle East and Eastern Africa has resulted in mutual penetration of cultural, economic, and political influences. In more recent times, it is assumed that the Middle East has influenced Eastern Africa more. Do the distinct regional traits, and what are currently considered asymmetrical relations, eliminate the possibility of developing equal and mutually respectful relationship between the two different but deeply intertwined regions? To answer this question and attempt to contribute to the debate on the intersection and the dynamics underpinning contemporary relations, we explore links between the two regions through historically conscious reflections. We argue for leveraging productively on the complex and deeply entrenched inter-regional ties by engagement based on equality, respect, and mutual benefit. ____ Historicamente, a interação entre Médio Oriente e África Oriental resultou na penetração mútua de influências culturais, económicas e políticas. Em tempos contemporâneos, supõe-se que o Médio Oriente tenha influenciado mais a África Oriental. Será que os traços regionais distintos, e o que hoje são consideradas relações assimétricas, eliminam a possibilidade de desenvolver relações iguais e mutuamente respeitosas entre as duas regiões diferentes, mas profundamente entrelaçadas? Para responder a esta questão e tentar contribuir para o debate sobre a intersecção e as dinâmicas que sustentam as relações contemporâneas, exploramos os vínculos entre as duas regiões através de reflexões historicamente conscientes. Defendemos o aproveitamento produtivo dos laços inter-regionais complexos e profundamente arraigados através de engajamento baseado na igualdade, respeito e benefício mútuo.